Differences of Passive Ankle Stiffness in Post-Stroke Hemiplegia by Varying Angular Velocity between the Paretic and Non-Paretic Side (Medico Legal Update, 2020)
Background/Objectives: The purpose of this study was to investigate the effect of passive stiffness on joint function by analyzing the in the passive stiffness of the PS and NPS ankle joint at various angular velocity.Method/Statistical Analysis: The differences of the stiffness of ankle according to different angular velocity in both sides were compared and analyzed in 11 hemiplegic patients. Analyses on the difference of stiffness of ankle joint at each angular velocity between the P and NP side were performed using a paired t-test. The ANOVA with repeated measure was performed to analyze the differences of the stiffness. Statistical significance was defined as P< .05.Findings: In the comparison on the passive stiffness of ankle joint, the paretic side was turned out to be higher in the passive stiffness than the non-paretic side at all angular velocity (20, 40, 60 deg/sec, P< .05). In addition, the analysis on the differences of the stiffness according to the changes in angular velocity showed that the stiffness was found to be the largest at 60 deg/sec and the smallest at 20 deg/sec in both paretic and non-paretic side indicating that the stiffness increases in the higher velocity (P< .05).These results indicate that the range of movement of paralyzed muscles caused by stroke is limited due to the increased passive ankle stiffness and that the velocity of movement is related to the joint function.Improvements/Applications: This study can be exploited as a basis to evaluate the passive ankle stiffness of paretic muscles of stroke patients affecting joint function and as a data for rehabilitation program.